Economic Integration in a Chamberlinian-Ricardian World - Toru Kikuchi (Economics and Econometrics Research Institute (EERI), 2008)
Based on a many-industry Chamberlinian-Ricardian trade model with iceberg trade costs, this note examines the impact of two modes of economic integration: a reduction in trade costs, and technical standardization due to information spillover. It is shown that these two modes of economic integration have opposing effects on specialization patterns: while trade liberalization narrows the range of industries with intra-industry trade, technical standardization widens the same range.
Keywords: D43; F12; 330; Monopolistic competition; Technical heterogeneity; Trade costs; Economic integration